A Zr, Mg, Mo-doped lithium-rich manganese-based positive electrode material and preparation method thereof

By doping Zr, Mg, and Mo elements into the lithium-rich manganese-based positive electrode material, the problem of capacity and voltage attenuation of layered lithium-rich manganese-based positive electrode material during the cycle process is solved, and long cycle stability and low voltage attenuation are achieved. Reduces the use of cobalt and improves the safety and cost-effectiveness of the material.

CN119008930BActive Publication Date: 2025-02-18JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479090.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing layered lithium-rich manganese-based positive electrode materials have severe capacity and voltage attenuation during the cycle, resulting in a short cycle life. At the same time, the high demand and toxicity of cobalt elements are seriously polluted to the environment, and it is necessary to develop cobalt-free or low-cobalt positive electrode materials. to improve safety and reduce costs.

Method used

Using Zr, Mg, and Mo doped lithium-rich manganese-based positive electrode material, the electrochemical strain between the two phases is balanced by doping elements, the lattice oxygen oxidation behavior is reconstructed, the catalytic reaction of the electrode electrolyte interface is shielded, the material structure is stabilized, and the material structure is improved. Electrochemical properties.

Benefits of technology

The long cycle stability and low voltage attenuation of Zr, Mg, and Mo doped lithium-rich manganese-based positive electrode materials under high current density are achieved, reducing the use of cobalt elements and improving the safety and cost-effectiveness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008930B_ABST
    Figure CN119008930B_ABST
Patent Text Reader

Abstract

The present invention is applicable to the technical field of modification of positive electrode materials for lithium-ion batteries, and provides a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material and a preparation method thereof. The morphology of the lithium-rich manganese-based positive electrode material is secondary particles formed by the accumulation of primary particles, with a primary particle size of 50 to 200 nm and a secondary particle size of 8 to 12 μm. The present invention synthesizes a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material using a simple and feasible method, which is applied in the field of lithium-ion batteries. As a positive electrode material for lithium-ion batteries, it exhibits ultra-long cycle capacity stability, small voltage decay, and shielded electrode electrolyte interface catalytic reaction. The present invention is of great significance to promoting the development of the selective doping approach to improve the electrochemical performance of lithium-ion battery positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode material modification, and in particular relates to a Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] In order to solve the environmental problems caused by fossil energy and achieve sustainable social development, the development of high-performance battery technology has become an urgent need. With the increasing demand for rechargeable lithium-ion batteries (LIBs) in electric vehicles, energy storage networks, electronic devices, etc., improving the energy density of LIBs, maintaining their cycle stability, improving their safety, and reducing their costs have become the main challenges of the industry. Layered lithium-rich manganese-based cathode materials (LMR) have high theoretical capacity (>250mAh / g) and high energy density (900Wh / kg) due to the joint participation of anions and cations in redox, but due to its two-phase composite structure, the electrochemical activity is severely unevenly distributed in the crystal, and LMR will experience severe capacity and voltage decay during the cycle, which will reduce its cycle life. Based on the current understanding of LMR, it is believed that the voltage decay is caused by the nanostrain between the composite two-phase crystal domains, which will lead to irreversible oxygen release, transition metal ion (TM) migration and structural rearrangement and other destructive effects, resulting in the high initial capacity of LMR cannot be maintained.

[0003] The stock of cobalt in the earth's crust is only 0.001% (mass ratio). The rapid increase in industry demand has caused its cost to continue to rise. In addition, cobalt is highly toxic and seriously pollutes the environment. This poses a major challenge to the industrial production of low-cost, environmentally friendly and sustainable batteries. Reducing the cobalt content of LIBs has become one of the ways to improve its safety and reduce costs. Therefore, developing cobalt-free positive electrode materials and compensating for their lack of stability due to the lack of cobalt through modification, thereby improving their performance has become one of the current goals of developing cobalt-free positive electrode materials. Element doping can effectively balance the electrochemical strain between the composite two phases, reconstruct the lattice oxygen oxidation behavior, shield the catalytic reaction at the electrode electrolyte interface, stabilize the evolution of the crystal structure of the LMR material during the cycle, and improve its electrochemical performance. For this purpose, a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material and a preparation method thereof are proposed. Summary of the invention

[0004] The object of the present invention is to provide a Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material and a preparation method thereof, aiming to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material, the chemical formula of the lithium-rich manganese-based positive electrode material is Li1.2 Ni 0.2 Mn 0.6-x (Zr, Mg, Mo) x O2, x is between 0.004 and 0.012.

[0007] Furthermore, the morphology of the lithium-rich manganese-based positive electrode material is secondary particles formed by the accumulation of primary particles, the primary particle size is 50-200 nm, and the secondary particle size is 8-12 μm.

[0008] Furthermore, the lithium-rich manganese-based positive electrode material has an initial coulombic efficiency of no less than 85% at a current density of 20 mA / g, and a capacity retention rate of more than 99% after 500 cycles at a current density of 200 mA / g.

[0009] A method for preparing the Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material according to the above-mentioned method comprises the following steps:

[0010] Step S1, adding a commercial nickel-manganese precursor into anhydrous ethanol, ultrasonically dispersing, and then stirring at a constant temperature;

[0011] Step S2, slowly adding a certain amount of Zr alcohol ester into the mixture while stirring, and placing the obtained system in air and stirring at a constant temperature for a certain period of time;

[0012] Step S3: After stirring, transfer the system into a reactor and add a certain amount of magnesium salt powder and (NH4)6Mo7O 24 4H2O, solvothermal reaction at 160~180℃, reaction time 8~12h;

[0013] Step S4, after filtering, washing and drying, the solvent thermal reaction product is mixed with Li2CO3 and a certain amount of flux and ground, then calcined at a high temperature of 700-900°C, and naturally cooled to room temperature;

[0014] Step S5: washing the calcined product with water and then drying it to finally obtain a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material.

[0015] Furthermore, in step S2, the amount of Zr alcohol ester used satisfies that the Zr atomic ratio is not higher than 1.5% of the product metal atoms.

[0016] Furthermore, in step S3, the amount of magnesium salt powder used satisfies that the Mg atomic ratio is not higher than 2% of the product metal atoms, (NH4)6Mo7O 24 The amount of 4H2O used is such that the Mo atomic ratio is no more than 2% of the product metal atoms.

[0017] Furthermore, in step S4, the amount of Li2CO3 added is 5-10% more than the stoichiometric ratio, the amount of flux added is 400% of the molar number of metal atoms of the target product, and the flux includes KCl and NaCl, and the molar ratio of KCl to NaCl is 3:2.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] Compared with the existing doped lithium-rich manganese-based materials, the present invention uses a simple and feasible method to synthesize Zr, Mg, and Mo doped lithium-rich manganese-based positive electrode materials, which are applied in the field of lithium-ion batteries. As a positive electrode material for lithium-ion batteries, it exhibits ultra-long cycle capacity stability, small voltage decay, and shielded electrode electrolyte interface catalytic reaction. The present invention is of great significance to promoting the development of the selective doping idea to improve the electrochemical performance of lithium-ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD diagrams of the doped electrode materials obtained in Examples 1 to 4.

[0021] Figure 2 These are SEM images of the doped electrode materials obtained in Examples 1 to 4.

[0022] Figure 3 This is the first charge and discharge of the doped electrode materials obtained in Examples 1 to 4 under 0.1C (20 mA / g current density) conditions.

[0023] Figure 4 For Li 1.2 Ni 0.2 Mn 0.6 O2 and Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 Comparison of the cycling performance of two samples of O2-B at a current density of 200mA / g.

[0024] Figure 5 For Li 1.2 Ni 0.2 Mn 0.6 O2 and Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 Comparison of rate performance of two samples of O2-B. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0027] One embodiment of the present invention provides a Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material, the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.2 Mn 0.6-x (Zr, Mg, Mo) x O2, x is between 0.004 and 0.012.

[0028] As a preferred embodiment of the present invention, the morphology of the lithium-rich manganese-based positive electrode material is secondary particles formed by the accumulation of primary particles, the primary particle size is 50-200 nm, and the secondary particle size is 8-12 μm.

[0029] As a preferred embodiment of the present invention, the lithium-rich manganese-based positive electrode material has an initial coulombic efficiency of not less than 85% at a current density of 20 mA / g, and a capacity retention rate of more than 99% after 500 cycles at a current density of 200 mA / g.

[0030] A method for preparing the Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material according to the above-mentioned method comprises the following steps:

[0031] Step S1, adding a commercial nickel-manganese precursor into anhydrous ethanol, ultrasonically dispersing, and then stirring at a constant temperature;

[0032] Step S2, slowly adding a certain amount of Zr alcohol ester to the mixture while keeping stirring, and placing the resulting system in air and stirring at a constant temperature for a certain period of time; in the step S2, the amount of Zr alcohol ester is such that the Zr atomic ratio is not higher than 1.5% of the product metal atoms.

[0033] Step S3: After stirring, transfer the system into a reactor and add a certain amount of magnesium salt powder and (NH4)6Mo7O 24 ·4H2O, and a solvent thermal reaction is carried out at 160-180°C for 8-12 hours; in step S3, the amount of magnesium salt powder used satisfies that the Mg atomic ratio is not higher than 2% of the product metal atoms, (NH4)6Mo7O 24 The amount of 4H2O used is such that the Mo atomic ratio is no more than 2% of the product metal atoms.

[0034] Step S4, after filtering, washing and drying, the solvent thermal reaction product is mixed with Li2CO3 and a certain amount of flux and ground, then calcined at a high temperature of 700-900°C, and naturally cooled to room temperature; in the step S4, the amount of Li2CO3 added is 5-10% more than the stoichiometric ratio, the amount of flux added is 400% of the molar number of metal atoms of the target product, and the flux includes KCl and NaCl, and the molar ratio of KCl to NaCl is 3:2.

[0035] Step S5: washing the calcined product with water and then drying it to finally obtain a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material.

[0036] In the embodiments of the present invention, the three doping elements Zr, Mg, and Mo have different doping selectivities in the two phases of the lithium-rich material, and their respective diffusion rates during high-temperature sintering are also different, thereby forming selective doping between the two phases and constructing a spinel phase on the particle surface. These structural designs reconstruct the anion oxidation capacity composition during the first charge process, weaken the catalytic reaction at the electrode electrolyte interface, and at the same time, through the in-situ diffusion of the spinel phase, reduce the structural degradation during the cycle, thereby achieving the stability of the long cycle of the layered lithium-rich manganese-based material.

[0037] Example 1: A lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 The preparation method of O2 comprises the following steps:

[0038] S1. Mix and grind the commercial nickel-manganese precursor with Li2CO3, KCl and NaCl, wherein Li2CO3 is in excess of 5% by mole, and then calcine at 850°C for 12h, and cool naturally to room temperature;

[0039] S2. Wash, filter and dry the calcined product to obtain the target product.

[0040] Example 2: A lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.588 Mg 0.01 Mo 0.002 The preparation method of O2 comprises the following steps:

[0041] S1. Add the commercial nickel-manganese precursor into the reactor, add 1% metal atomic ratio of magnesium salt powder and 1% metal atomic ratio of (NH4)6Mo7O 24 4H2O, solvothermal reaction with ethanol as solvent for 12h;

[0042] S2. The solvent thermal reaction product is filtered, washed and dried, then mixed and ground with KCl, NaCl and 5% molar excess Li2CO3, then calcined at 850°C for 12h and naturally cooled to room temperature.

[0043] S3, washing, filtering and drying the product obtained by calcination to obtain the target product.

[0044] Example 3: A lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The preparation method of O2-A comprises the following steps:

[0045] S1. Add the commercial nickel-manganese precursor into the reactor, add 1% metal atomic ratio of ZrO2, 1% metal atomic ratio of MgCO3 and 1.5% metal atomic ratio of (NH4)6Mo7O 24 4H2O, solvothermal reaction with ethanol as solvent for 12h;

[0046] S2. The solvent thermal reaction product was filtered, washed and dried, then mixed and ground with KCl, NaCl and 5% molar excess of Li2CO3, and then calcined at 850°C for 12h and cooled naturally to room temperature;

[0047] S3, washing, filtering and drying the product obtained by calcination to obtain the target product.

[0048] Example 4: A lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The preparation method of O2-B comprises the following steps:

[0049] S1. Add the commercial nickel-manganese precursor into anhydrous ethanol, disperse it by ultrasonic, and then stir it at a constant temperature of 60°C;

[0050] S2. Slowly add 1% metal atomic ratio of Zr(C3H7O)4 while stirring, and place the resulting system in air at a constant temperature of 60°C and stir for 5 hours;

[0051] S3. After the stirring is completed, the system is transferred into a reactor and 1% metal atomic ratio of MgCO3 and 1.5% metal atomic ratio of (NH4)6Mo7O are added. 24 4H2O, solvothermal reaction for 12h;

[0052] S4, the solvent thermal reaction product is filtered, washed and dried, mixed and ground with KCl, NaCl and 5% molar excess Li2CO3, and then calcined at 850°C for 12h, and naturally cooled to room temperature;

[0053] S5. Wash, filter and dry the calcined product to obtain the target product.

[0054] Embodiment 5: A method of using Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The method for preparing a button cell using an O2-B lithium-rich manganese-based positive electrode material comprises the following steps:

[0055] Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The O2-B positive electrode material is mixed with 10% by mass of conductive carbon and a binder, and a certain amount of N-methylpyrrolidone solution is added. After stirring evenly, the mixture is coated on aluminum foil and dried in a vacuum oven. Then the electrode sheets are cut out with a slicer. The electrodes are transferred to a glove box with an argon atmosphere, and assembled into button cells using lithium metal sheets as counter electrodes, glass fiber filter paper as diaphragm, and a mixed solution of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate of lithium hexafluorophosphate as electrolyte.

[0056] The Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The mass ratio of O2-B cathode material to binder and Li 1. 2Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The mass ratio of O2-B positive electrode material to conductive agent is 8:1.

[0057] The binder is polyvinylidene fluoride, and the conductive agent is acetylene black.

[0058] Figure 1 The XRD patterns of the doped electrode materials obtained in Examples 1 to 4 are shown below. Figure 1 It can be seen that the XRD of the doped electrode materials prepared in Examples 1 to 4 all show characteristic peaks of the lithium-rich material structure, and the doping of Zr, Mg and Mo does not change the crystal structure of the material.

[0059] Figure 2 The following are SEM images of the doped electrode materials obtained in Examples 1 to 4. Figure 2 It can be seen that the doped electrode materials prepared in Examples 1 to 4 are all composed of secondary particle balls of 8 to 10 μm, and the doping of Zr, Mg, and Mo elements does not change the microscopic morphology of the materials.

[0060] Figure 3 The first charge and discharge of the doped electrode materials prepared in Examples 1 to 4 under 0.1C (20 mA / g current density) conditions. Figure 3 It can be seen that, firstly, Zr, Mg, and Mo doping changed the shape of the high voltage (>4.5V) charging curve and reconstructed the oxidation behavior of lattice oxygen. Secondly, Mg and Mo doping reduced the first discharge capacity of the electrode material. After the introduction of Zr, the attenuation of the first capacity can be effectively suppressed. The co-doping of Zr, Mg, and Mo elements improved the coulombic efficiency of the first cycle, while Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 The first coulombic efficiency of O2-B can reach as high as 95.7%.

[0061] Figure 4 For Li 1.2 Ni 0.2 Mn 0.6 O2 and Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 Comparison of the cycling performance of the two samples O2-B at a current density of 200mA / g. Figure 4 It can be seen that Li co-doped with Zr, Mg, and Mo 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo 0.004 O2-B achieves the stability of lithium-rich materials in extremely long cycles, and its capacity remains 100% after 500 cycles.

[0062] Figure 5 For Li 1.2 Ni 0.2 Mn 0.6 O2 and Li 1.2 Ni 0.2 Mn 0.576 Zr 0.008 Mg 0.012 Mo0.004 Comparison of rate performance of two samples O2-B. Figure 5 It can be seen that the co-doping of Zr, Mg and Mo elements achieves the improvement of the rate performance of lithium-rich materials, and the initial capacity can still be fully restored after recovering to a small rate.

[0063] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a Zr, Mg, Mo-doped lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: Step S1, adding a commercial nickel-manganese precursor into anhydrous ethanol, ultrasonically dispersing, and then stirring at a constant temperature; Step S2, slowly adding a certain amount of Zr alcohol ester into the mixture while stirring, and placing the obtained system in air and stirring at a constant temperature for a certain period of time; Step S3: After stirring, transfer the system into a reactor and add a certain amount of magnesium salt powder and (NH4)6Mo7O 24 4H2O, solvothermal reaction at 160~180℃, reaction time 8~12h; Step S4, after filtering, washing and drying, the solvent thermal reaction product is mixed with Li2CO3 and a certain amount of flux and ground, then calcined at a high temperature of 700-900°C, and naturally cooled to room temperature; Step S5, washing the calcined product with water, and then drying it to finally obtain a Zr, Mg, and Mo-doped lithium-rich manganese-based positive electrode material; The chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.2 Mn 0.6-x (Zr, Mg, Mo) x O2, x is between 0.004 and 0.

012.

2. The method for preparing a Zr, Mg, Mo-doped lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the step S4, the amount of Li2CO3 added is 5-10% more than the stoichiometric ratio, and the flux includes KCl and NaCl, and the molar ratio of KCl to NaCl is 3:

2.

3. A Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material prepared by the preparation method of Zr, Mg, Mo doped lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.2 Mn 0.6-x (Zr, Mg, Mo) x O2, x is between 0.004 and 0.

012.

4. The Zr, Mg, Mo-doped lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The morphology of the lithium-rich manganese-based positive electrode material is secondary particles formed by the accumulation of primary particles, the size of the primary particles is 50-200 nm, and the size of the secondary particles is 8-12 μm.

Citation Information

Patent Citations

  • Composite lithium-rich positive electrode material and preparation method and application thereof

    CN111509206A

  • Lithium ion battery positive electrode material, preparation method and application thereof

    CN116207247A